MiR-18a-LncRNA NONRATG-022419 pairs targeted PRG-1 regulates diabetic induced cognitive impairment by regulating NGF\BDNF-Trkb signaling pathway - Qiong Xiang; Hu Lin; Jia-Sheng Tao; Chuan-Jun Fu; Li-Ni Liu; Jing Deng; Xian-Hui Li (Proteome Science)
Abstract Background Diabetic encephalopathy (DE) is considered as one of the complications of diabetes,which is associated with cognitive impairment in the pathological process of development. Up to now, phospholipid phosphatase related 4 (Plppr4), also known as plasticity related gene 1 (PRG-1) has been revealed its important role in neuroplasticity. However, the underlying mechanisms of Plppr4 on the basis of diabetic-induced cognitive dysfunction (DCD) are still unknown. The aim of current study was to provide insight into molecular mechanism and cellular heterogeneity underlying DCD, and investigate the functional role of PRG-1 involved in this process. Methods Combined Single-cell RNA sequencing (scRNA-seq) and RNA transcriptome analysis, the distinct sub-populations, functional heterogeneity as well as potential enriched signaling pathways of hippocampal cells could be elucidated. Results We identified the sub-cluster of type I spiral ganglion neurons expressed marker gene as Amigo2 in cluster8 and Cnr1 in cluster 9 of hippocampal cells from DCD and the effect of those on neuronal cells interaction. We also found that PRG-1 was involved in the synaptic plasticity regulation of hippocampus via NGF\BDNF-Trkb signaling pathway. In high glucose induced HT22 cells injury model in vitro, we investigated that down-regulated PRG-1 along with down-regulated BDNF and also decreased expression of synapsin-1, PSD-95, SYN which are related to synaptic plasticity; Meanwhile, the Prg-1 targeted miR-18a-LncRNA NONRATG-022419 pairs related with significantly down-regulated expression of PRG-1. Conclusion This study revealed the synaptic plasticity regulation of PRG-1 in DCD, and might provide the therapeutic target and potential biomarkers for early interventions in DCD patients.